Oxford handbook of paediatrics - Tasker, Robert C. (Robert Charles), 1958-; Acerini, Carlo L.; Holloway, Edward; Shah, Asma; Lilitos, Pete (New York, NY : Oxford University Press, 2020)
This third edition of the'Oxford Handbook of Paediatrics' is a compact, pocket-sized compendium of clinical problems and treatment options from a team of specialist contributors and editors with years of clinical experience. Taking a child-centred approach, the practical advice and know-how contained within this handbook will be invaluable to all those involved in the care of the younger patient. Fully revised and updated, this edition of the handbook provides vital information on areas such as neonatology, surgery, genetics and congenital malformations, and child protection in a user-friendly and succinct style.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 15, 2020).
Keywords: Pediatrics